Moldova Socioemotional Skills Assessment - World Bank (World Bank, Washington, DC, 2019)
Moldovan employers voice concerns that workers’ low levels of socioemotional capabilities, such as poor work ethics, lack of motivation, and limited problem-solving skills, are among the major constraints for business development and productivity. The World Bank’s 2013 Business Environment and Enterprise Performance Survey, the 2016 Labor Market Forecast of Moldova, and a qualitative interview among private sector representatives in 2017 suggest that employers face skills shortages, particularly in areas of work ethics, motivation, and problem solving. The magnitude of skills shortages in Moldova is the highest in the Europe and Central Asia region. The Moldovan labor market will benefit from an increased supply of employees, including new recruits, with a range of relevant socioemotional as well as cognitive capabilities. This report provides a first diagnostic of socioemotional skills in Moldova to profile the skills composition of grade 9 students, identify learning context measures that are strongly associated with socioemotional skills, and clarify options for policy makers and practitioners to foster socioemotional skills. To this end, the Moldovan Socioemotional Skills Assessment was launched in April 2019. This assessment focused on grade 9 students to better understand how much socioemotional skills students exiting the end of the compulsory school cycle self-reported, and how these skills were associated with learning inputs from schools and families. This assessment was the first to evaluate a range of socioemotional skills among school-age children in Moldova, using measures that had been validated internationally. The measures were designed to capture five broad domains of socioemotional skills, including students’ self-reported capacity to ‘work with others’, ‘care for others’, ‘engage with others’, ‘explore new horizons’, and ‘manage emotions. The assessment provided not only technical validation of the measurement tools in Moldova but also initial guidance for policies and practices to foster these skills. The results suggest that such measurement tools can be mobilized in Moldova in the future.